2011
DOI: 10.1007/s11250-011-9782-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrate supplementation on performance, ovarian response, and some biochemical profile of Malpura ewes

Abstract: Effect of feed flushing on ovulation rate was investigated during the autumn seasons on 24 adult Malpura ewes (BW 34.8 ± 0.58 kg and age 4-7 years) equally divided into two groups. Ewes in G1 (group 1) were grazed 8-10 h daily on Cenchrus ciliaris pasture interspersed with seasonal shrub. In addition to grazing, concentrate was provided at 1.5% of BW to the animals in G2 (group 2) for a period of 35 days. Estrus was synchronized by a double injection schedule of PGF(2α) at 0 and 10 days of the experiment and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Sejian et al, [35] opined that prolonged restriction of dietary energy lengthened postpartum estrus period in cattle and sheep, possibly by suppression of the increase in LH pulse frequency that was necessary for growth of ovarian follicles to the pre-ovulatory stage. The findings in the present study agree to some extent to the observations made by Naqvi et al, [36] which showed that by providing supplemental nutrition to pasture grazing ewes for 14 days before lambing and 21 days postpartum, the time to postpartum estrus was shorter, though non-significant (p≥0.10) for the supplemented group during dry season (46.9±2.7 vs. 52.9±2.6 day), while in wet season, it was significantly (p<0.07) shorter for the supplemented group (33.0±3.1 vs. 41.1±2.9 day).…”
Section: Post-partum Onset Of Estrussupporting
confidence: 94%
“…Sejian et al, [35] opined that prolonged restriction of dietary energy lengthened postpartum estrus period in cattle and sheep, possibly by suppression of the increase in LH pulse frequency that was necessary for growth of ovarian follicles to the pre-ovulatory stage. The findings in the present study agree to some extent to the observations made by Naqvi et al, [36] which showed that by providing supplemental nutrition to pasture grazing ewes for 14 days before lambing and 21 days postpartum, the time to postpartum estrus was shorter, though non-significant (p≥0.10) for the supplemented group during dry season (46.9±2.7 vs. 52.9±2.6 day), while in wet season, it was significantly (p<0.07) shorter for the supplemented group (33.0±3.1 vs. 41.1±2.9 day).…”
Section: Post-partum Onset Of Estrussupporting
confidence: 94%
“…Usually, the endocrine glands are stimulated following water restriction with the sole purpose of modifying the metabolic activities depending on the ambient temperature [91]. Alteration in follicular growth and by extension, reduced oestrus cycle, has been linked to negative energy balance and reduced feed intake resulting from water deprivation [92]. Oestrus duration in Kivircik sheep in the semi-arid region was reduced when feed intake drops (30.00% of ad libitum intake) [93].…”
Section: Adaptive Responses Of Small Ruminants To Water Shortages mentioning
confidence: 99%
“…Results of present study are in line with Kia et al (2011) who studied that increase in live body weight in three different breeds of sheep when given high (130 % of the metabolizable energy for maintenance) and moderate (70 % of the metabolizable energy for maintenance) nutritional supplementation for 6 weeks before mating with grazing on low-nutritive pasture. Naqvi et al (2011) maintained sheep on pasture with low quality dry herbage along with nutritional supplementation and reported that during period of flushing nutritionally deprive ewes gained weight in an efficient and rapid way. Naqvi et al (2016) reviewed the relationship between reproduction and nutrition, Furthermore, there is several nutritionally associated signals work as messengers fundamental in reproduction process (Hess et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Rivas-Muñoz et al, (2010) found that high protein diet can increase ovulation rate in ewes than high-energy ration. Naqvi et al (2011) reported that feed supplementation or nutritional flushing before mating increases ovulation rates and lambing percentage in many sheep breeds. Acero-Camelo et al (2008) did flushing of Merino breeds of sheep for three weeks and reported that 23% higher lambing rate.…”
Section: Resultsmentioning
confidence: 99%